In-vivo Evaluation of the Wound Healing Activity of the Sesamum Indicum L. Seed Extract in Novel Ethosomal Vesicular System - Somwanshi, Sachin B; Hiremath, Shivanand N (Journal of Drug Delivery and Therapeutics, 2018)
Aim: To establish the wound healing activity of Sesamum indicum L. of seed extract in novel ethosomal vesicles. Methods: The ethosomal vesicles were formulated with prepared seed extract of Sesamum indicum L. by solvent evaporation method and characterized it. The optimized ethosomal vesicles then incorporated into gel base for further in vivo study in wistar rat. The evaluation of the wound healing activity was performed by using two models i.e. incision and excision models. In excision model percentage wound contraction and period of epithelialization were established for both the extracts. In incision model the parameter which was carried out was breaking strength of wounded skin. Results: The results revealed that the percentage wound contraction, period of epithelialization in excision model was enhanced than that of other groups and tensile strength of skin in incision model was similar to that of standard treated group. Keywords: Sesamum indicum L., Wound Healing, Ethosomal gel.